Layar Merapi: Encouraging disaster preparedness through open-air cinema initiatives in Dukun Subdistrict - Arifianto, Budi Dwi; Utami, Citra Dewi; Muktaf, Zein Mufarih (Community Empowerment, 2025)
Dukun Subdistrict is one of the areas with a high level of vulnerability to Mount Merapi eruptions. The low understanding of technical disaster mitigation terms among rural communities, particularly those in the KRB III (Third Zone of Disaster-Prone Area), served as the foundation for implementing the "Layar Merapi" program. This community service initiative utilizes open-air cinema screenings, combined with educational sessions and performances of local cultural arts, to foster disaster preparedness. The program was conducted in six villages, employing an educational, participatory, and culture-based approach. The results indicate that this initiative successfully increased the community's collective understanding of disaster mitigation and strengthened social networks among village residents.